Growth differentiation factor-15 as a biomarker of atherosclerotic coronary plaque: Value in people living with and without HIV - Royston, Léna; Isnard, Stéphane; Perrin, Nils; Sinyavskaya, Liliya; Berini, Carolina; Lin, John; Trottier, Benoit; Baril, Jean-Guy; Chartrand-Lefebvre, Carl; Tremblay, Cecile; Durand, Madeleine; Routy, Jean-Pierre (Frontiers in Cardiovascular Medicine, 2022)
Background: Increased rates of cardiovascular diseases (CVD) and larger subclinical high-risk coronary plaques in coronary CT angiography have been observed in people living with HIV (PLWH) treated with antiretroviral therapy (ART) compared to HIV-uninfected people. Growth differentiation factor-15 (GDF-15) is a cytokine emerging as an optimal marker for CVD in the general population. Methods: We cross-sectionally analyzed plasma of 95 PLWH on ART and 52 controls. We measured GDF-15, fibroblast growth factor-21 (FGF-21), glucagon-like peptide-2 (GLP-2), soluble urokinase plasminogen activator receptor (suPAR), CRP and anti-CMV and anti-EBV IgG levels. All participants had no clinical CVD and underwent coronary CT angiography with 3D reconstruction of coronary artery atherosclerotic plaques. Total plaque volume (TPV) and low attenuation plaque volume (LAPV, defined as density < 30 Hounsfield Units) were calculated (mm3). Results: In both PLWH and controls, GDF-15 levels were increased in participants with presence of coronary plaque vs without (p=0.04 and p<0.001, respectively) and correlated with TPV (r=0.27, p=0.009 and r=0.62, p<0.001, respectively) and LAPV (r=0.28, p=0.008, r=0.60, p<0.001, respectively). However, in a multivariate model, GDF-15 was independently associated with LAPV in controls only (adjusted OR 35.1, p=0.04) and not in PLWH, mainly due to confounding by smoking. Other markers were not independently associated with plaque volume, except for anti-EBV IgGs in controls (adjusted OR 3.51, p=0.02). Conclusion: In PLWH, GDF-15 and smoking seemed to synergistically contribute to coronary plaque volume. Conversely, increased GDF-15 levels were associated with the presence of coronary artery plaques in people without HIV, independently of CV risk factors.